Drip Irrigation as a Potential Alternative to Traditional Irrigation Method for Saline Water Usage in Vegetable Crops- A Review - Seema,; Dahiya, Rita; Prakash, Ram; Sheoran, H. S.; Roohi, (International Journal of Economic Plants, 2022)
The aim of this review was to understand the response of various vegetable crops to different salinity and nitrogen levels under drip and traditional methods of irrigation. Effective methods of irrigation water application are important that would allow the proper use of poor-quality water for sustainable production. Drip irrigation is an economically feasible technology for water-saving (40%) and increasing the yield (30-40%) in different crops. Various research studies found that the salt concentration of irrigation water was negatively correlated with growth, fruit yield and quality parameters of vegetable crops. Further, the plants which received 100% of recommended dose of fertigation under saline water irrigation showed a better performance in terms of higher nutrient uptake of nitrogen (150.09- 226.26 kg ha-1), phosphorous (13.67-74.64 kg ha-1), and potassium (155.70-302.05 kg ha-1) with highest water use efficiency (11.9 - 61.68 kg ha-1 m-1). We made an attempt to review and compile the ill effects of saline water application and also summarise management strategies to manage poor quality water in vegetable production, especially in arid and semi-arid regions. The review also highlighted the importance of drip irrigation as an alternative to conventional methods for efficient use of poor-quality water without adversely affecting the quality and productivity of vegetable crops.